Legal protection of the child of unknown parentage: Between Algerian legislation and international conventions - Atik, Nadira (The International tax journal, 2025)
There is no doubt that among the important topics that impose themselves in the area of law is the question of protection the child of unknown parentage, which has received varying degrees of attention and care in national legislations and international conventions. This necessitates research and shedding light on the issue of legal protection concerning this child, whether in Algerian legislation or in international conventions.